2013
DOI: 10.1007/s40309-013-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

Limits to prediction: Europeanizing technology in an expert forum

Abstract: EU expert institutions delivering policy advice about the promise of emerging technologies, help frame the issues that technologies might address. Their assumptions about European contexts for technology futures therefore warrant critical attention. Drawing on current theoretical work in science and technology studies, archival research and interviews with policy actors, this article examines the European Commission's recently established European Technology Platforms. It focuses in particular on the industry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…To address the shortcomings of the traditional vector space model, researchers have proposed a number of methods to quantify the weight of feature words. Reference [17] proposed to construct a knowledge-based vector space model by combining similarity measures of average distance, position weighting, and edge counting to construct relationships among words in documents; the study in [18] proposed a new text representation model to reduce matrix dimensionality and computational complexity by implementing text feature word synonymy merging; the study in [19] represented documents into a three-layer model to reduce the high-dimensional word frequency information to low-dimensional information, so as to extract the semantic information of words in the document and then perform text clustering on this basis; the study in [20] determines the feature words by using similarity testing methods according to the composition structure and position of noun phrases; the study in [21] obtains the features of products in reviews by using association rules from customer reviews of products through text mining and calculate the number of reviews with two types of emotions for each feature, so as to form a summary of product features. A domain term of information extraction is used, and some feature word pruning algorithms are added as an aid to represent the feature words [22].…”
Section: Related Studiesmentioning
confidence: 99%
“…To address the shortcomings of the traditional vector space model, researchers have proposed a number of methods to quantify the weight of feature words. Reference [17] proposed to construct a knowledge-based vector space model by combining similarity measures of average distance, position weighting, and edge counting to construct relationships among words in documents; the study in [18] proposed a new text representation model to reduce matrix dimensionality and computational complexity by implementing text feature word synonymy merging; the study in [19] represented documents into a three-layer model to reduce the high-dimensional word frequency information to low-dimensional information, so as to extract the semantic information of words in the document and then perform text clustering on this basis; the study in [20] determines the feature words by using similarity testing methods according to the composition structure and position of noun phrases; the study in [21] obtains the features of products in reviews by using association rules from customer reviews of products through text mining and calculate the number of reviews with two types of emotions for each feature, so as to form a summary of product features. A domain term of information extraction is used, and some feature word pruning algorithms are added as an aid to represent the feature words [22].…”
Section: Related Studiesmentioning
confidence: 99%
“…This study has identified topics in visions on desirable and sustainable futures, which were authored by citizens in connection to three European projects: Civisti, Casi and Cimulact. Involving citizens in such foresight provides a parallel and analogous procedure to expert envisioning [14] and could be further institutionalised to an established form of foresight [2]. The benefits of considering participatory processes in backcasting exercises such as those performed in the examined projects have been observed before [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is similarly important to recognise that citizen contributions to foresight evolve over time and vary according to context. This, in turn, provides an empirically identified rationale to institutionalise citizen involvement in foresight [2]. Of course, organisers of citizen involvement should be aware of the effects of their project aims on the outcomes of the involvement and not naively see their results as fully representative or neutral.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interpretative flexibilities of emerging technologies vary in their amenability to different groups' agendas and needs (Pinch and Bijker 1984;Bijker 2010). The meanings and associations they evoke can help sustain particular sociotechnical imaginaries (Jasanoff and Kim 2013), influence the credibility of promises of technological solutions to complex problems (Markusson et al 2017), and lend cohesion to expert communities and organizations (Gjefsen 2013. Their role should thus be acknowledged in any analysis of the contexts of research communication.…”
Section: Literaturementioning
confidence: 99%